2021
DOI: 10.3390/foods10050994
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Origin and Organic Attributes of Extra Virgin Olive Oil: A Choice Experiment in the Italian Market

Abstract: The paper investigates Italian consumers’ behavior towards characteristics of extra virgin olive oil, in particular organic production methods and geographical origin. On the basis of the existing literature, the concepts of sustainability of food systems, diets, and the olive oil supply chain are analyzed. A choice experiment (CE), using a face-to-face questionnaire with over 1000 participants, was conducted to quantify the willingness to pay (WTP) for these two attributes. Findings show positive preference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 79 publications
4
10
1
2
Order By: Relevance
“…Although quality is a multidimensional aspect, consumers' knowledge of attributes that differentiate different types of olive oil are important, particularly those that are easily detectable through taste and flavor. In a recent Italian study [11], even though 73% of the participants stated that they knew the characteristics of EVOO, only just above 50% were able to correctly recognize those characteristics that distinguish this product. In general, previous surveys in Greece have described consumers' preferences, attitudes, and perceptions about olive oil characteristics [19]; consumers' perception regarding olive oil authenticity [20]; and the economic and socio-spatial attributes that affect consumers' choices on purchasing olive oil from the supermarket or from a friend/relative or consuming their own production [10].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Although quality is a multidimensional aspect, consumers' knowledge of attributes that differentiate different types of olive oil are important, particularly those that are easily detectable through taste and flavor. In a recent Italian study [11], even though 73% of the participants stated that they knew the characteristics of EVOO, only just above 50% were able to correctly recognize those characteristics that distinguish this product. In general, previous surveys in Greece have described consumers' preferences, attitudes, and perceptions about olive oil characteristics [19]; consumers' perception regarding olive oil authenticity [20]; and the economic and socio-spatial attributes that affect consumers' choices on purchasing olive oil from the supermarket or from a friend/relative or consuming their own production [10].…”
Section: Introductionmentioning
confidence: 91%
“…Krystallis and Ness [13], for example, reported that the most valued attributes of olive oil among Greek consumers were geographical origin and organic production, with price being among the least valued. A recent survey [11] reported that Italian consumers had similarly a positive preference for geographical origin attribute, but, on the other hand, the organic attribute was not highly valued. Other attributes, such as oil color [14] and low-acidity [15] as well as attributes such as market leader brand, sustainability, and supply chain ethics [11], have also been reported as important olive oil preference attributes.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Development of organic or local food products with upcycled ingredients could potentially be the right way to increase the probability of consumers' acceptance. Indeed, Carzedda et al [14] investigated Italian consumers' behavior towards EVOO organic production methods and geographical origin to quantify the willingness to pay for these two attributes. Findings showed positive preference for origin attributes, especially linked to local productions.…”
mentioning
confidence: 99%